Use of dual-task methodology for skill assessment and development: Examples from rugby league - Gabbett, T.; Wake, M.; Abernethy, B. (Journal of Sports Sciences, 2011)
We assessed the attentional demands of drawing and passing in rugby league players and investigated the effects of single-task and dual-task training on the acquisition, retention, and transfer of skill in these athletes. In Study 1, high-skilled and lesser-skilled rugby league players performed a standardized 2-on-1 drill under single-task (primary skill in isolation) and dual-task (primary skill while performing a secondary verbal tone recognition task) conditions. No differences were detected in primary task performance between groups, although the performance of the high-skilled players was more resistant to skill decrement under dual-task conditions. In Study 2, high-performance rugby league players were randomly allocated to either a single-task or dual-task training group. Each group underwent 8 weeks of training between the pre- and post-test sessions. While the mean improvement for draw and pass proficiency under dual-task conditions in the dual-task training group was greater than in the single-task training group (10.0% vs. 2.3%), the differences, while providing a moderate effect size (d = 0.57), were not statistically significant. These results suggest that the attentional demands of drawing and passing are reduced in high-skilled rugby league players compared with their lesser-skilled counterparts. In addition, compared with single-task training, dual-task training appears to improve the ability to perform dual-task draw and pass tasks (possibly through an improvement in time-sharing skills). Further studies are required to verify the efficacy of dual-task training as a training stimulus.